Knowledge regarding childhood autism among Montessori teachers in Biratnagar, Nepal - Ghimire, Samita; Chhetri, Mamta; Paudel, Amrita (Janaki Medical College Journal of Medical Science, 2026)
Background & Objectives: Autism is one of the neurodevelopmental diseases that have been included under the umbrella term autism spectrum disorder (ASD). Early diagnosis of the child is possible only when people who are directly involved with the child are aware about autism. The aim of study was to assess knowledge about childhood autism among Montessori teachers. Materials and Methods: Descriptive cross-sectional study was conducted May 1st to May 15th, 2019, using face to face interview in Biratnagar Metropolitan city. Total List of Montessori schools was obtained along with the teachers one week prior to data collection. There was total 17 Montessori schools according to information provided by education section of metropolitan office. There was total 144 Montessori teachers and complete enumeration was carried out, and total of 132 Montessori teachers were participants for the study. Response rate was (91.6%). We used pearsons chi square test and binary logistic regression analysis to assess knowledge about childhood autism among Montessori teachers in Biratnagar Metropolitan City. All data were coded, entered, and then analyzed using the Statistical Package for Social Sciences (SPSS; Chicago, IL, USA) program, version 20. Results: Among 132 Montessori teachers 31.8% (42) had adequate level of knowledge ,43.9% (58) had moderately adequate and 24.2% (32) had inadequate level of knowledge. Level of knowledge was significantly associated with Montessori training (0.035), training related to autism (<0.01), prior contact (<0.001). Conclusions: There was inadequacy of knowledge about Autism among Montessori teachers. As in present day most of the parents are working so they tend to send their children to Montessori from very early age expecting better care. Hence Montessori teachers need to have knowledge about various developmental disorders that occur among children in which autism is among one of them.